THREE YEAR MORTALITY ANALYSIS AMONG HEMODIALYSIS PATIENTS: A SINGLE CENTER STUDY FROM MULTAN INSTITUTE OF KIDNEY DISEASES - ASGHAR, MR; ANWAR, S; BASHIR, K; SALEEM, N (Biological and Clinical Sciences Research Journal, 2023)
This study evaluated the mortality among registered hemodialysis patients in a single center at Multan Institute Of Kidney Diseases (MIKD) Multan in south Punjab, Pakistan. A Retrospective cohort study was conducted at Multan Institute of Kidney Diseases, Multan, from 22 January 2019 to 22 December 2021 in three years. All adult patients of End-stage renal disease (ESRD) maintained on hemodialysis for more than three months registered with the dialysis unit of MIKD irrespective of their age, gender, serology with the biochemical test, morbidity, and cause of mortality were recorded in the study. SPSS version 22 was used for data entry and analysis. A p-value≥0.05 was considered significant. The ethical review committee approved the study ref# 08-14 dated 01-01-2022 to consent from all the included patients. Out of these 110 deaths, the mean age was 52.14±14.75, and male gender 80 (72.7%) were predominantly noted. Hypertension was the most common morbidity, followed by diabetes and diabetic nephropathy 103 (93.6%), 56 (50.9%), and 54 (49.1%), respectively. Predominant biochemical parameters of expired hemodialysis patients were hyperphosphatemia 64 (58.2%), anemia 51 (46.4%), hypoalbuminemia 43 (39.1%), hypocalcemia 35 (31.8%) and hypoparathyroidism 33 (30%). The leading cause of death was cardiovascular, 38 (34.5%). The most common viral marker in CVA was HBs Ag; HCV was the most common in CVD death patients (p<0.001).The relative risk of mortality in the HD population is 20.6 times to the general population. The risk variables can be monitored and intervened on in a timely manner to reduce mortality in the future.